Bitcoin Generation using Blockchain Technology - Balajee Maram (JOIV : International Journal on Informatics Visualization, 2018)
There are limitations in client-server model of communication. Distributed architecture provides good accessibility to all the nodes in the network. A blockchain technology is follows distributed model. In the digital era, all the transactions are available in the digital form is called a ledger. This ledger belongs to all the users in the network are shared by all the users in the network. Every transaction is monitored and verified by every user in the network. The blockchain is a chain of blocks that contains a collection of transactions. Bitcoin is a cryptocurrency, depends on blockchain technology. The Bitcoins are generated from the mining of a block for the miner. Every user knows about each and every Bitcoin transaction in the blockchain network. The block is immutable, because every block is verified by each customer in the blockchain network. This is the initiation for new trend for security to the digital transactions in the world. This paper presents the logic in the blockchain and Bitcoin generation process using blockchain technology.